SINDROM WAARDENBURG DISERTAI MIKROPENIS - MOHAMMAD BHERBUDI WICAKSONO (LP2MTBM MAKARIOZ, 2023)
Pediatric patients with Waardenburg syndrome and micropenis face quality of life issues and disease morbidity. Interventions and regular monitoring are needed to improve the child's quality of life. A 14-year-old boy, diagnosed with Waardenburg syndrome since the age of 12 based on clinical findings of blue right iris, hypopigmentation in the thoracic region, testicular undesensus, micropenis, port wine stain on the forehead and occipital region, and hearing loss. The patient had not visited the hospital for 8 years. At the age of 8 years (in 2008) a BERA examination was performed with the results of abnormal AS and AD hearing threshold values, corresponding to severe hearing loss with damage to N.VIII (severe deafness), abdominal ultrasound showed UDT sinistra, no testicular images were seen in the bilateral scrotum, bilateral inguinal, pelvis, to the middle abdomen Observation and intervention were carried out to determine the course of Waardenburg Syndrome and micropenis. Intervention of hearing correction with hearing aids and testosterone hormone injection for once every 3 weeks in 3 months starting from February 2017 to April 2017. The injection was given intra muscularly 25 mg in the gluteus area, side effects of action, side effects of therapy and improving quality of life. The patient's condition at the beginning of observation, has been diagnosed with waardenburg syndrome and micropenis, with secondary sex development in Tanner 1, child PedsQL 42, IQ 75, speech sound disorder, not confident, good nutrition. The results of intervention and monitoring for 18 months were hearing aid fitting, testosterone hormone therapy, Tanner scale 3, IQ 92 speech sound disorder improved, good nutrition, and improved quality of life. This can be achieved due to good therapy compliance from patients and families.Intervention and continuous routine observation are important in improving the lives of patients with Waardenburg syndrome and micropenis.